Toll-Like Receptor 3 Signal in Dendritic Cells Benefits Cancer Immunotherapy - Matsumoto, Misako; Takeda, Yohei; Tatematsu, Megumi; Seya, Tsukasa (Frontiers in Immunology, 2017)
Pattern recognition receptors (PRRs) play a crucial role in the innate immune system and contribute to host defense against microbial infection. PRR-mediated anti-microbial signals provide robust type I IFN/cytokine production and trigger inflammation, thereby affecting tumor progression and autoimmune diseases. Accumulating evidence demonstrates that among the PRRs, only the signaling pathway of endosomal Toll-like receptor 3 (TLR3) induces no systemic inflammation and mediates cross-priming of antigen-specific CD8+ T cells by dendritic cells. Treatment with a newly-developed TLR3-specific ligand, ARNAX, along with tumor-associated antigens (TAAs), induces tumor-specific cytotoxic T lymphocytes, modulates the tumor microenvironment to establish Th1-type anti-tumor immunity, and leads to tumor regression without inflammation in mouse tumor models. Combination therapy using ARNAX/TAA and PD-1/PD-L1 blockade potently enhances anti-tumor response and overcomes anti-PD-1/PD-L1 resistance. In this review, we will discuss the TLR3-mediated signaling in anti-tumor immunity and its application to cancer immunotherapy.